ANALISIS KINERJA BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA (BPMPD) KABUPATEN PELALAWAN DALAM PENGELOLAAN BANTUAN PEMBANGUNAN DESA TERPADU TAHUN 2013-2015 - Dedy Setiawan; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of this research is to get the performance of Community Empowerment and Village Government (BPMPD) of Pelalawan Regency in Integrated Village Development Assistance Management without having to see the big amount of budget produced. The implementation of this program has not been implemented in an optimal manner that is not effective in the Village Community Empowerment and Village Government Pelalawan District. This research uses qualitative approach, this research type is descriptive research. The focus of the research is the performance or human resources available at the Village Community Empowerment and Village Administration Agency Pelalawan District. The informants in this research are the Head of Community Empowerment and Village Governance, Documentation. Data analysis technique used in this research is descriptive analysis technique. The results showed that the implementation of village development assistance management in measuring from the perspective of performance program of Community Empowerment Board and Village Government can not be said good because it can not do development equally. The recommendation of this research is for human resources of Community Empowerment and Village Government of Pelalawan Regency is expected that its performance does not decrease and for the village community is expected participation and cooperation in village development effort conducted by Community Empowerment Board and Village Government Pelalawan RegencyKeywords: Performance, and Human Resources